The Correlation of Body Height Estimation ond Forearm Length of The Mandailing Batak Tribe in Medan City - Lubis, Adriansyah; Julanda, Baari Putra; Septiawan, Dedi Andika (Universitas Baiturrahmah, 2025)
The victim identification process is needed to recognize and differentiate the victim from another one. Formulation height estimation is one of the components that can be identified. Long bone measurements such as the forearm are determined to have better results for measuring the height estimation. This study aims to determine the correlation of height estimation with forearm length measurement of the Mandailing Batak tribe in Medan City. A cross-sectional study was performed using 86 sample people. Chi-square Pearson and Spearman tests were used for statistical analysis. There was a significant correlation of height estimation with forearm length with p <0.05.